ANALISIS HUBUNGAN KEKERABATAN DURIAN (Durio zibethinus Murr.)BERDASARKAN PENANDA MORFOLOGI DI KABUPATEN KUANTAN SINGINGI - Nasri Baroroh; Fitmawati '; Nery Sofiyanti (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Durian (Durio zibethinus Murr.) is one of tropical fruit belongs to Bombacaceae family that has high economic value. Kuantan Singingi District one of durian distribution areas in Riau Province which has high diversity of durian. The purpose of this study was to identify the diversity of durian in Kuantan Singingi District. This study had been conducted from August 2013 to February 2014. Sampling was done using purposive random sampling and observation on morphological characters. Morphological data was analyzed by SIMQUAL and UPGMA procedures using the program NTSYS-pc. 2:02 and followed by correlation analysis, variability and principal components using Minitab 16:13. From a total of 32 individuals of durian, the similarity coefficient was ranged from 23% to 64%. The dendrogram formed two main groups that clustered based on the similarity of morphological characters. Pearson correlation analysis obtained 14 characters of 61 characters which were positively correlated with each other with the level of confidence was >98%. Result of principal component analysis formed two groups with 30% of the diversity value.